Long‐term outcomes of 54 dogs with tracheal collapse treated with a continuous extraluminal tracheal prosthesis. Issue 5 (21st May 2019) - Suematsu, Masahiro; Suematsu, Hiroaki; Minamoto, Tomomi; Machida, Noboru; Hirao, Daiki; Fujiki, Makoto
Abstract: Objective: To describe the surgical placement of a continuous extraluminal tracheal prosthesis (CETP) and report the subsequent postoperative clinical outcomes in dogs with tracheal collapse. Study design: Retrospective case series. Animals: Fifty‐four dogs. Methods: Medical records of dogs in which cervical and/or thoracic inlet tracheal collapse was diagnosed and treated by placement of a CETP between 2010 and 2017 were reviewed to evaluate postoperative complications, changes in respiratory function, and survival. Histological examinations of tracheal tissues performed in 2 dogs at 51 and 57 months after surgery were also reviewed. Results: Fifty‐three (98%) dogs survived to discharge. Postoperative complications included laryngeal paralysis (1 dog), disseminated intravascular coagulation (1 dog), and recurrent tracheal collapse (2 dogs). None of the dogs exhibited clinical evidence of tracheal necrosis. Preoperative dry, harsh cough resolved in 87% of the dogs after surgery. Goose honking cough was resolved in 25 of 26 (96%) dogs. Median follow‐up time was 30 months (range, 16 days to 76 months). The survival rate at 36 months was 86% (CI: 75%‐96%). On histological examination in 2 dogs, the tracheal tissue surrounding the prosthesis was well preserved and without evidence of chronic inflammation. Conclusion: Continuous extraluminal tracheal prosthesis placement in dogs with tracheal collapse resulted in low postoperative complication rates and good long‐term outcomes. Clinical significance: Continuous extraluminal tracheal prosthesis placement provides a viable alternative surgical option for managing dogs with tracheal collapse.